Long-Term Financial Incentives and Investment in Daughters : Evidence from Conditional Cash Transfers in North India - Sinha, Nistha; Yoong, Joanne (2012)
Since the early 1990s, several states in India have introduced financial incentive programs to discourage son preference among parents and encourage investment in daughters' education and health. This study evaluates one such program in the state of Haryana, Apni Beti Apna Dhan (Our Daughter, Our Wealth). Since 1994, eligible parents in Haryana have been offered a financial incentive if they give birth to a daughter. The incentive consists of an immediate cash grant and a long-term savings bond redeemable on the daughter's 18th birthday provided she is unmarried, with additional bonuses for education. Although no specific program participation data are available, we estimate early intent-to-treat program effects on mothers (sex ratio among live children, fertility preferences) and children (mother's use of antenatal care, survival, nutritional status, immunization, schooling) using statewide household survey data on fertility and child health, and constructing proxies for household and individual program eligibility. The results based on this limited data imply that Apni Beti Apna Dhan had a positive effect on the sex ratio of living children, but inconclusive effects on mothers' preferences for having female children as well as total desired fertility. The findings also show that parents increased their investment in daughters' human capital as a result of the program. Families made greater post-natal health investments in eligible girls, with some mixed evidence of improving health status in the short and medium term. Further evidence also suggests that the early cohort of eligible school-age girls was not significantly more likely to attend school; however, conditional on first attending any school, they may be more likely to continue their education.